Behaviour of Clinical, Anthropometric and Laboratory Variables in Patients with Metabolic Syndrome - Madelaine Hernández Tamayo; Pedro Enrique Miguel Soca; Mildre María Marrero Hidalgo; Luz María Pérez López; Idania Peña Pérez; Mayelín Rivas Estévez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: Diagnosing patients with metabolic syndrome is important because of the high prevalence and risk they present. Objective: to determine the behaviour of some clinical, anthropometric and laboratory variables in patients with metabolic syndrome. Methods: A descriptive study was conducted. The sample included 161 patients selected at random in different research stages from a universe including all the patients who attended six different consultations in Urbano Noris municipality, Holguín, from September 2008 to June 2009. Diagnosis was performed according to the ATP-III. Variance analysis and Fisher's exact test in SPSS (α = 0.05) were applied. Results: Patients with metabolic syndrome (n = 103: 63.97%) presented values over average weight, height, waist circumference, body mass index, systolic blood pressure, plasma cholesterol, LDL, triglycerides and glucose. Their HDL levels were lower. A significant association between metabolic syndrome and CRP, microalbuminuria, alterations in blood sugar levels and hypertension was proved. Conclusions: The importance of characterizing the metabolic syndrome for future interventions was determined.